2012
DOI: 10.1038/ncomms2249
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic blastomere behaviour reflects human embryo ploidy by the four-cell stage

Abstract: Previous studies have demonstrated that aneuploidy in human embryos is surprisingly frequent with 50–80% of cleavage-stage human embryos carrying an abnormal chromosome number. Here we combine non-invasive time-lapse imaging with karyotypic reconstruction of all blastomeres in four-cell human embryos to address the hypothesis that blastomere behaviour may reflect ploidy during the first two cleavage divisions. We demonstrate that precise cell cycle parameter timing is observed in all euploid embryos to the fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
314
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(329 citation statements)
references
References 52 publications
(90 reference statements)
14
314
0
1
Order By: Relevance
“…Mertzanidou et al found that 3/27 (11%) of cleavage stage embryos carried a meiotic abnormality, a figure that is in line with other researchers, for instance Chavez et al [45] who found 9/45 four-cell embryos to carry a meiotic abnormality. The majority of abnormalities found were therefore of post-zygotic and mosaic in origin: between 46% [45] and 87% [10] seem to be mitotic abnormalities. Mitotic non-disjunction seemed to be less frequent than previously assumed, and endoreduplication followed by a cellular division with multipolar spindles was proposed as a mechanism leading to chaotic karyotypes [9].…”
Section: Array Comparative Genomic Hybridisation (Acgh)supporting
confidence: 75%
See 2 more Smart Citations
“…Mertzanidou et al found that 3/27 (11%) of cleavage stage embryos carried a meiotic abnormality, a figure that is in line with other researchers, for instance Chavez et al [45] who found 9/45 four-cell embryos to carry a meiotic abnormality. The majority of abnormalities found were therefore of post-zygotic and mosaic in origin: between 46% [45] and 87% [10] seem to be mitotic abnormalities. Mitotic non-disjunction seemed to be less frequent than previously assumed, and endoreduplication followed by a cellular division with multipolar spindles was proposed as a mechanism leading to chaotic karyotypes [9].…”
Section: Array Comparative Genomic Hybridisation (Acgh)supporting
confidence: 75%
“…Array CGH was also an important tool to start to understand the origin of post-zygotic chromosomal abnormalities in embryos. By arraying every cell of cleavage stage embryos, it was found that the majority of cleavage stage embryos were chromosomally abnormal [9,10,[44][45][46]. Mertzanidou et al found that 3/27 (11%) of cleavage stage embryos carried a meiotic abnormality, a figure that is in line with other researchers, for instance Chavez et al [45] who found 9/45 four-cell embryos to carry a meiotic abnormality.…”
Section: Array Comparative Genomic Hybridisation (Acgh)supporting
confidence: 60%
See 1 more Smart Citation
“…This suggests abnormal distribution of chromosomes during first mitosis. Chavez et al [10] observed that the generation of partial chromosomal gains and losses were restricted primarily to embryos with mitotic errors. During the first mitotic divisions in human preimplantation development, improper segregation of chromosomes might occur, causing high rates of aneuploidy and mosaicism [11].…”
Section: Resultsmentioning
confidence: 99%
“…The timing of key parameters from time-lapse monitoring for predictions of blastocyst formation [11][12][13] aneuploidy, [14,15], and, in some cases, implantation [16][17][18] have been investigated. Various models based on specific developmental milestones and phenotypes have been built [9].…”
Section: Available Time-lapse Systems and Potential Benefitsmentioning
confidence: 99%